[WHAT'S HAPPENING?] I'M FEELING EMOTIONAL. (1st June 2019) - Battle, Christina
[What's Happening?] I'm feeling emotionallooks to how animated GIFS, used as emotional aides in online conversation, might be changing the ways that we relate. While the reliance on GIFs as stand-ins for emotional expressions may be a way to build the social back into online communication and a reaffirmation of the role of emotion in society as an important and even critical requirement; the essay considers how the over representation of fictional characters, animals, and cultural stereotypes selected by algorithms may be shifting culture in ways we haven't yet realized.